Advantageous selection in crop insurance: Theory and evidence - He, Juan; Rejesus, Roderick; Zheng, Xiaoyong; Yorobe, Jose (Wiley, 2018)
We extend the recently proposed multi‐dimensional asymmetric information model to show that advantageous selection could be present in crop insurance with two types of coverage: (i) multiple perils (e.g. a multi‐peril, ‘all risk’ policy), and (ii) a specific named peril (or set of perils). Our theoretical model suggests that certain characteristics of an insured farmer (or farm) under both types of coverage can be sources of advantageous selection. Farmers who advantageously select are more likely to purchase insurance coverage and less likely to realise a loss. A supplementary empirical analysis, based on data from the Philippine crop insurance market, illustrates how sources of advantageous selection can be identified econometrically.